Does the national health insurance scheme in Ghana reduce household cost of treating malaria in the Kassena-Nankana districts? - Maxwell Ayindenaba Dalaba; Patricia Akweongo; Raymond Aborigo; Timothy Awine; Daniel Kweku Azongo; Prosper Asaana; Frank Atuguba; Abraham Oduro (Global Health Action, 2014)
Introduction: The Government of Ghana introduced the National Health Insurance Scheme (NHIS) in 2003 to replace out-of-pocket (OOP) payment for health services with the inherent aim of reducing the direct cost of treating illness to households. Objective: To assess the effects of the NHIS in reducing cost of treating malaria to households in the Kassena-Nankana districts of northern Ghana. Methods: We conducted a cross-sectional survey between October 2009 and October 2011 in the Kassena-Nankana districts. A sample of 4,226 households was randomly drawn from the Navrongo Health and Demographic Surveillance System household database and administered a structured interview. The costs of malaria treatment were collected from the patient perspective. Results: Of the 4,226 households visited, a total of 1,324 (31%) household members reported fever and 51% (675) reported treatment for malaria and provided information on where they sought care. Most respondents sought malaria treatment from formal health facilities 63% (424), with the remainder either self-medicating with drugs from chemical shops 32% (217) or with leftover drugs or herbs 5% (34). Most of those who sought care from formal health facilities were insured 79% (334). The average direct medical cost of treating malaria was GH¢3.2 (US$2.1) per case with the insured spending less (GH¢2.6/US$1.7) per case than the uninsured (GH¢3.2/US$2.1). The overall average cost (direct and indirect) incurred by households per malaria treatment was GH¢20.9 (US$13.9). Though the insured accounted for a larger proportion of admissions at health facilities 76% (31) than the uninsured 24% (10), the average amount households spent on the insured was less (GH¢4/US$2.7) than their uninsured counterparts (GH¢6.4/US$4.3). The difference was not statistically significant (p=0.2330). Conclusion: Even though some insured individuals made OOP payments for direct medical care, there is evidence that the NHIS has a protective effect on cost (outpatient and in-patient) of malaria treatment.